Motorcycle jack - Mohd Fadhli, Che Ismail (2009)
These reports present about develop and make the motorcycle jack. This motorcycle jack is developing to ease for make maintenance toward motorcycle such as change engine oil, change tire and fork oil change and other. For make a motorcycle jack, it has many process included such as measuring process, cutting process, joining process, drilling process and painting process. This motorcycle made by adjusting and upgrades the motorcycle jacks that already have in market. This project also required analysis to ensure the strength and safety of the product meet the user need. To be confirm that the motorcycle jack safe and can be used, a stress analysis have be done to study about maximum stress. By using mild steel, it can be producing following the characteristic and specification.